Quantitative and qualitative measurement of carbon compounds in dust emitted in the work environment for electrical insulators production factory - Ahmed, Ali Shihab; Shukri, Hussein Mahmood; Salih, Zeina Tariq (Journal of natural sciences, life and applied sciences, 2020)
A quantitative and qualitative determination of the pollutants emitted within the work environment, including dust and its components of organic and inorganic carbon was conducted in one of the factories of electrical insulators production. A dust sampler and 5 micron diameter filters were used and prepared for analysis in the carbon analyzer of organic and inorganic components. The result of the analysis shows the dust emissions concentrations of organic carbon (OC) in the mechanical lathing unit for cutting Phenolic Carbon Insulators (PCI) is (244.0 µg.m-3) and the lowest inorganic emissions (59.0 µg.m-3). The emission of manual filings from inorganic carbon dust is the highest concentration (916.0 µg.m-3) and the lowest organic carbon is (4.0 µg. m-3). The highest level for total inorganic carbon (TIC) in the manual unit fillings is (440.0 mg.m-3. .8hr-1) and the lowest TIC concentration is (2.8 mg.m-3. .8hr-1) in the mechanical lathing unit for phenolic carbon. While the highest level for OC in the mechanical lathing unit is (117.0 mg.m-3. .8hr-1) and the lowest OC concentration is (2.0 mg.m-3..8hr-1) in manual and pressing units. All concentrations of the dust and their components of organic and inorganic carbon are out of standards limitation of the International Standards Units (ISU). Exposure to these emissions during an actual working time of 8 hours a day requires commitments to individual and group safety measures to maintain workers safety.